Addition of rosella flower (Hibiscus sabdariffa) powder addition on the quality of bulk cooking oil - Fardani, Roushandy Asri; P.P, Hendry Satria (UNIVERSITAS MUHAMMADIYAH MATARAM, 2022)
Oil is used as a medium for frying food that is widely consumed by the public. One way to overcome rancidity by improving the quality of oil by using antioxidants. Antioxidants consist of synthetic antioxidants and natural antioxidants. The use of synthetic antioxidants such as BHA (Butyl Hydroxy Anisol) and BHT (Butyl Hydroxy Toulene) raises many concerns about side effects such as causing swelling of the liver and affecting enzyme activity. Therefore, it is necessary to look for other alternatives, namely natural antioxidants. Natural antioxidants are antioxidants extracted from natural plant and microbial materials. One of the plants that has the potential to be utilized as a natural antioxidant is Rosella Flower. This aims of this study was to determine the effect of adding rosella flower powder as a natural antioxidant and to determine the quality of bulk cooking oil after adding Rosella Flower Powder to bulk cooking oil stored for 0 and 7 days. This study uses the Iodometric Titration method, data obtained by statistical tests and comparison with Indonesian National Standard number 01-3741-2013. The results of the analysis with Post hoc LSD test showed that the use of rosella flower powder almost equaled BHT and was said to be one group.